2009
DOI: 10.1093/nar/gkp571
|View full text |Cite
|
Sign up to set email alerts
|

The role of deadenylation in the degradation of unstable mRNAs in trypanosomes

Abstract: Removal of the poly(A) tail is the first step in the degradation of many eukaryotic mRNAs. In metazoans and yeast, the Ccr4/Caf1/Not complex has the predominant deadenylase activity, while the Pan2/Pan3 complex may trim poly(A) tails to the correct size, or initiate deadenylation. In trypanosomes, turnover of several constitutively-expressed or long-lived mRNAs is not affected by depletion of the 5′–3′ exoribonuclease XRNA, but is almost completely inhibited by depletion of the deadenylase CAF1. In contrast, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
97
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(105 citation statements)
references
References 113 publications
(158 reference statements)
7
97
0
1
Order By: Relevance
“…Several studies revealed a biphasic decay pattern for EP1 mRNA in bloodstream forms and identified the nucleases involved [27][28][29]46]. In one of our experiments, a decay pattern reminiscent of biphasic decay kinetics was found for GPEET mRNA in late PF (with only 0.4% GPEET-positive cells) (Fig.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Several studies revealed a biphasic decay pattern for EP1 mRNA in bloodstream forms and identified the nucleases involved [27][28][29]46]. In one of our experiments, a decay pattern reminiscent of biphasic decay kinetics was found for GPEET mRNA in late PF (with only 0.4% GPEET-positive cells) (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…An identical mechanism was considered for the fast decay of EP1 mRNA in bloodstream form T. brucei [26], but this was not confirmed by a subsequent study [28]. However, degradation of unstable Leishmania transcripts bearing a retroposon-derived instability motif in their 3 UTR appears to be initiated by endonucleolytic cleavages at discrete sites [48].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Trypanosomes are therefore an ideal model system for the analysis of mRNA turnover. They have homologs of deadenylases (Milone et al 2004;Schwede et al 2008Schwede et al , 2009) and the exosome (Clayton and Estevez 2010) and three potential homologs of Xrn1, XRNA, XRNB, and XRNC (Li et al 2006). Of these, XRNA was shown to be essential for the growth of both life cycle stage forms of T. brucei and for the degradation of two highly unstable developmentally regulated mRNAs (Li et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, XRNA was shown to be essential for the growth of both life cycle stage forms of T. brucei and for the degradation of two highly unstable developmentally regulated mRNAs (Li et al 2006). More detailed analysis revealed that the unstable EP mRNA was degraded from both the 59 and 39 ends (Schwede et al 2009). …”
Section: Introductionmentioning
confidence: 99%